Workshop on enriching the Ministry of Higher Education’s concept papers. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2005)
IPPTN was recently requested by the Ministry of Higher Education to prepare five concept papers related to higher education. The institute subsequently formed five committees comprising several researchers from public and private institutions of higher learning to discuss and prepare the following papers.